Reproductive systems and low outbreeding barriers between Jacaranda cuspidifolia and J. mimosifolia (Jacarandeae, Bignoniaceae) - Bittencourt Junior, Nelson Sabino [UNESP] (Wiley-Blackwell, 2019)
The genus Jacaranda shows notable karyotype stability and a prevailing self-sterile breeding system with evidence of late-acting self-incompatibility in several species. However, some studies have indicated self-compatibility in J. mimosifolia, a species cultivated worldwide in tropical and subtropical areas. Jacaranda cuspidifolia is a closely related species with natural distribution broadly overlapping with that of J. mimosifolia, and manual heterospecific pollination studies have indicated that these species are interfertile, but there is no report on the breeding system of the former. In this study, we used hand-pollination experiments, pistil longevity, epi-fluorescence and histological analysis of post-pollination events to determine the breeding system of J. cuspidifolia. We also employed intra and interspecific crosses and seed germination tests to reevaluate the breeding system of J. mimosifolia and the inter-fertility between the two species. Some fruits were initiated from self-pollinated pistils in J. mimosifolia, but none of them reached maturity. On the other hand, complete absence of fruit development by self-pollination was verified in J. cuspidifolia, while in situ pollen tube growth and histological analysis of post-pollination events in selfed pistils revealed the characteristic ovule penetration, fertilization and endosperm initiation also observed in other bignoniaceous species with late-acting self-incompatibility. Low outbreeding barriers seem to operate between these species because reciprocal interspecific crosses and hybrid seed germination tests indicated they are bilaterally interfertile. However, fruit/seed production and seed germinability were significantly lower when pistils of J. cuspidifolia were pollinated with pollen of J. mimosifolia, compared with crosses in the opposite direction, which indicates a partial unilateral incompatibility. This result is discussed in the context of the possible occurrence of self-compatibility in J. mimosifolia. The low level of incongruity operating between the two species also points to their recent evolutionary divergence.
Keywords: heterospecific cross-compatibility; incongruity; inter-fertility; late-acting self-compatibility; low outbreeding barriers; unilateral incompatibility